The Role of Grammar in Learning-Teaching English: EFL Learners Belief - Arif, Nely -; Eddy Haryanto; Rosinta Norawati; Sri Wachyuni; Duti Volya (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This research aims to investigate the learners' beliefs dealing with the role of grammar in learning-teaching English at one State University in Jambi. The population of this study included English study program students at FKIP, Universitas Jambi, with the sample consisting of second-, third- and fourth-year students who have taken grammar courses. The questionnaire was used to get the quantitative data. To support the discussion of the findings obtained quantitatively, the interviews with 3 participants were conducted. Data of questionnaire were analyzed by Google Form Statistic and Excel Aplication. Meanwhile, qualitative data from interviews were analyzed with the help of the NVivo application. The data strongly indicate that EFL learners at the university where this research was conducted hold a shared belief in the crucial role of English grammar in their learning process. The specific emphasis is on writing skills, especially in academic and formal contexts. It provides valuable insights for language educators and policymakers in tailoring effective language education strategies for these learners. ABSTRAK Penelitian ini bertujuan untuk menyelidiki keyakinan peserta didik yang berhubungan dengan peran tata bahasa dalam belajar-mengajar bahasa Inggris di salah satu Universitas Negeri di Jambi. Populasi penelitian ini meliputi mahasiswa program studi bahasa Inggris di FKIP Universitas Jambi, dengan sampel terdiri dari mahasiswa tahun kedua, ketiga dan keempat yang telah mengambil mata kuliah tata bahasa. Kuesioner digunakan untuk mendapatkan data kuantitatif. Untuk mendukung pembahasan temuan yang diperoleh secara kuantitatif, dilakukan wawancara dengan 3 partisipan. Data kuesioner dianalisis dengan Google Form Statistic dan Excel Aplication. Sementara itu, data kualitatif hasil wawancara dianalisis dengan bantuan aplikasi NVivo. Data tersebut secara jelas menunjukkan bahwa pelajar EFL di universitas tempat penelitian ini dilakukan memiliki keyakinan bersama akan peran penting tata bahasa Inggris dalam proses pembelajaran mereka. Penekanan khusus adalah pada keterampilan menulis, terutama dalam konteks akademik dan formal. Ini memberikan wawasan berharga bagi pengajar bahasa dan pembuat kebijakan dalam menyesuaikan strategi pendidikan bahasa yang efektif untuk pelajar ini